Giant days. Volume twelve - Allison, John, 1976- (Boom! Box, 2020)
It<U+2019>s never a quiet day at the University of Sheffield as best friends Esther, Susan and Daisy try do regular things like solving comic book shop capers, attending McGraw<U+2019>s brother<U+2019>s wedding and Daisy learning to drive OH MY GOD WE<U+2019>RE ALL DOOMED. Meanwhile, Ed has to have a hard conversation with his girlfriend about her behavior when she drinks and what it means for their future<U+2026>if they have one.